Client Discretion, Switching Costs, and Financial Innovation - Bhattacharyya, Sugato; Nanda, Vikram (Review of Financial Studies, 2000)
We analyze the incentives of investment banks to develop innovative products. We show that client characteristics and market structure affect these incentives significantly. Investment banks with larger market shares have greater incentives to innovate and smaller banks are likely to share their innovations with the largest bank. Innovation incentives increase in volatile environments and regulatory scrutiny actually encourages loophole exploitation activity. Our predictions are consistent with stylized facts and the analysis has broad testable implications for innovative activity in other markets similarly characterized by a lack of comprehensive protection for intellectual property rights, for example, the software industry. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.